A novel ruthenium-tungsten bimetallic complex dye-sensitizer for photoelectrochemical cells application - Khuzaimah Arifin; Wan Ramli Wan Daud; Mohammad Kassim (Universiti Kebangsaan Malaysia, 2014)
A novel bimetallic double thiocyanate-bridged ruthenium and tungsten metal complex containing bipyridyl and dithiolene co-ligands was synthesized and the behavior of the complex as a dye-sensitizer for a photoelectrochemical (PEC) cell for a direct water splitting reaction was investigated. The ligands and metal complexes were characterized on the basis of elemental analysis as well as UV-Vis, Fourier transform infrared (FTIR) and nuclear magnetic resonance (1H and 13C NMR) spectroscopy. Cyclic voltammetry of the bimetallic complex showed multiple redox couples, in which half potentials E1/2 at 0.625, 0.05 and 0.61V were assigned as the formal redox processes of Ru(III)/Ru(II) reduction, W(IV)/W(V) and W(V)/W(VI) oxidations, respectively. Photocurrent measurements were performed in homogeneous system and TiO2 was used as the photoanode for photocurrent measurements. Current density generated by the bimetallic complex was higher than that of N3 commercial dye which suggested that the bimetallic complex donated more electrons to the semiconductor.